A tensile and aging resistant 1kv overhead insulated conductor
Patent Information
- Application Number
- CN202611065595.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-17
AI Technical Summary
[0018]1、耦合绝缘树脂在导体外周熔融包覆并冷却定型后,先形成连续且具有一定支撑能力的主体相,该主体相并非普通聚烯烃简单共混所得,而是由双活性聚烯烃母料与柔性硼酯基料进一步加工形成,因此在导线铺设、牵引、弯折及持续受载过程中,包覆层内部更易保持均衡的形变分配,局部应力不易集中于单一部位;儿茶酚协同硅粉进入该体系后,与树脂基体之间形成较为稳定的界面过渡,使受力状态下的应力传递路径更趋连续,由界面脱开、微裂纹萌生以及局部薄弱区扩展所引发的结构失稳情形相对减少,导体外周包覆层在往复受力条件下更易维持整体性与协调性。
Smart Images

Figure CN122575810B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductor manufacturing, specifically to a 1kV overhead insulated conductor that is tensile-resistant and aging-resistant. Background Technology
[0002] 1kV overhead insulated conductors are widely used in urban and rural power distribution networks and near-user transmission and distribution lines. They typically consist of a conductor layer and an insulation layer covering the outer perimeter of the conductor layer. The insulation material for this type of conductor is mostly made of polyethylene, ethylene-vinyl acetate copolymer and its modified resin system, and is processed and shaped with antioxidants, lubricating stabilizers and inorganic fillers to meet the basic requirements for insulation covering, mechanical support and electrical isolation under overhead laying conditions. The relevant materials are generally coated onto the conductor surface by melt extrusion, and after cooling and shaping, a continuous insulation layer is formed to ensure the insulation safety and stability of the conductor in the operating environment.
[0003] However, under actual operating conditions, 1kV overhead insulated conductors are subjected to tension traction, wind vibration, sun exposure and temperature fluctuations for extended periods. The insulation layer not only needs to have initial mechanical strength but also needs to maintain good structural continuity during continuous stress. Although some traditional insulation materials can meet the basic forming and coating requirements, their resin matrix has a relatively simple internal structure and limited interaction between different components. This leads to local stress concentration, uneven microstructure and insufficient interface bonding in the coating layer after repeated stress, which in turn affects the stable coverage of the conductor surface by the insulation layer and is not conducive to the long-term maintenance of tensile properties.
[0004] In addition, overhead insulated conductors are continuously subjected to the combined effects of hot air, oxidizing environment, and load temperature rise during long-term service. The insulation material needs to take into account the structural retention capacity under thermal aging conditions. In conventional systems, the degree of interfacial bonding between the resin phase and the filler phase is limited, and the density and uniformity of local areas are insufficient. After the accumulation of thermal effects, it is more likely to show phenomena such as structural relaxation, increased interfacial voids, and gradual expansion of weak parts. Such changes not only weaken the overall stability of the insulation layer, but also make it difficult to achieve synergistic maintenance between the mechanical property retention capacity and the insulation barrier state, thus restricting the long-term operational reliability of the conductor. Summary of the Invention
[0005] The purpose of this invention is to provide a 1kV overhead insulated conductor that is resistant to tensile stress and aging, in order to solve the technical problem that the tensile strength and aging resistance of overhead insulated conductors in the prior art need to be further improved.
[0006] The objective of this invention can be achieved through the following technical solution: a 1kV overhead insulated conductor with tensile strength and aging resistance, comprising a conductor layer and an insulation layer, wherein the conductor layer is made of aluminum and has a cross-sectional area of 50-60 mm².2 The insulation layer is obtained by melting and extruding the insulation material onto the surface of the copper conductor, and its thickness is 1.4-1.5 mm.
[0007] The insulating layer material comprises the following raw materials in parts by weight: 100 parts coupling insulating resin, 1-2 parts catechol synergistic silica powder, 0.21-0.32 parts antioxidant 1010, 0.21-0.32 parts antioxidant 168, and 0.12-0.15 parts calcium stearate, wherein the coupling insulating resin is a polyolefin-based resin containing a silane grafted structure, an anhydride grafted structure, and a borate ester dynamic coupling structure; and the catechol synergistic silica powder is a silica synergistic base material with a catechol functional layer on its surface.
[0008] Furthermore, the method for preparing the insulating layer is as follows: the insulating layer material is added to a mixer and stirred until uniform, and then the mixture is added to an extruder. The temperature of each temperature zone is controlled at 130-160℃, and the screw speed is 140-180r / min. The mixture is melt-extruded and coated onto the surface of the conductor layer to form an insulating layer.
[0009] Furthermore, the preparation method of the coupling insulating resin is as follows: add the dual-active polyolefin masterbatch into a mixer and melt mix for 2-3 minutes, then add the flexible borosilicate base material, and mix at 150-160℃ and 50-70 r / min for 4-7 minutes, and then perform post-treatment to obtain the coupling insulating resin.
[0010] Furthermore, the ratio of the dual-active polyolefin masterbatch to the flexible borosilicate base material is 450-550g:20-30g, and the post-processing includes: discharging after mixing, pressing and cooling, crushing and pelletizing to obtain coupling insulating resin with a particle size of 3.0-4.0mm.
[0011] Furthermore, the preparation method of the dual-active polyolefin masterbatch is as follows: low-density polyethylene and ethylene-vinyl acetate copolymer are added to a mixer and mixed evenly. Then, vinyltrimethoxysilane, maleic anhydride and dicumyl peroxide are mixed evenly and added to a twin-screw extruder. The temperature of each temperature zone is controlled at 145-180℃, the screw speed is 160-200 r / min, and the extrusion time is 4-8 min. The dual-active polyolefin masterbatch is obtained after post-treatment.
[0012] Furthermore, the ratio of low-density polyethylene, ethylene-vinyl acetate copolymer, vinyltrimethoxysilane, maleic anhydride, and dicumyl peroxide is 360-400g:140-160g:20-25mL:8-11g:2-3g. The post-processing includes: the extrudate is discharged from the machine under vacuum, cooled, stretched, pelletized, and dried in a drying oven at 50-60℃ for 2-4 hours to obtain a dual-active polyolefin masterbatch with a particle size of 3.0-4.0mm.
[0013] Furthermore, the preparation method of the flexible borosilicate base material is as follows: polypropylene glycol diglycidyl ether is added to a reaction vessel and stirred. After heating to 58-65℃, 3-amino-1,2-propanediol is added and stirred for 2.5-3.5h. Then, the temperature is raised to 85-92℃, 1,4-phenylenediboric acid is added in batches and stirred for 1.5-2.5h. The flexible borosilicate base material is obtained after post-treatment.
[0014] Furthermore, the ratio of polypropylene glycol diglycidyl ether, 3-amino-1,2-propanediol and 1,4-phenylenediboronic acid is 260-320 mL: 65-82 g: 45-60 g. The post-treatment includes: cooling to 55-65°C after the reaction and discharging the material, and drying the material in a vacuum drying oven at 60-70°C for 4-8 hours to obtain flexible boron ester base material.
[0015] Furthermore, the preparation method of the catechin-synergistic silica powder is as follows: deionized water and tris(hydroxymethyl)aminomethane are added to a reaction vessel and stirred. Then, the pH is adjusted to 8.4-8.6 using 10wt% hydrochloric acid aqueous solution, and anhydrous ethanol is added. After stirring evenly, silica is added for dispersion, and then dopamine hydrochloride is added. The mixture is kept at 28-35℃ and stirred for 4-8 hours. The catechin-synergistic silica powder is obtained after post-treatment.
[0016] Furthermore, the ratio of deionized water, tris(hydroxymethyl)aminomethane, anhydrous ethanol, silica, and dopamine hydrochloride is 800-1000 mL: 10-14 g: 250-350 mL: 50-70 g: 15-21 g. The post-treatment includes: after the reaction is completed, filtering and collecting the filter cake, washing the filter cake with anhydrous ethanol and deionized water 1-2 times in sequence, then drying it in a vacuum drying oven at 45-55℃ for 10-14 h, pulverizing it through a 200-mesh sieve to obtain catechol-co-silica powder.
[0017] The present invention has the following beneficial effects:
[0018] 1. After the coupling insulating resin melts and coats the outer periphery of the conductor and cools and solidifies, it first forms a continuous main phase with a certain supporting capacity. This main phase is not obtained by simple blending of ordinary polyolefins, but is formed by further processing of dual-active polyolefin masterbatch and flexible borosilicate base material. Therefore, during the laying, pulling, bending and continuous loading of the conductor, the inner layer of the coating layer is more likely to maintain a balanced deformation distribution, and local stress is less likely to concentrate in a single part. After catechol and silica powder enter the system, they form a relatively stable interface transition with the resin matrix, making the stress transmission path under stress more continuous. The structural instability caused by interface separation, microcrack initiation and local weak area expansion is relatively reduced. The outer periphery coating layer of the conductor is more likely to maintain integrity and coordination under reciprocating stress conditions.
[0019] 2. Under the combined service conditions of continuous heat and air environment, the coating layer of the coupled insulating resin is not prone to the concentrated shrinkage, local hardening, or embrittlement that occurs earlier in conventional polyolefin systems. Instead, it exhibits a relatively gentle structural evolution process. The continuous phase base formed by the dual-active polyolefin masterbatch and the adaptive structure after the introduction of the flexible borosilicate base material form a more coordinated internal configuration relationship after further coupling. This ensures that the local area and the overall structure maintain a good connection when the insulation layer undergoes thermal history. After catechol and silica powder are dispersed in the system, the maintenance effect on the interface area and microstructure is further manifested, which makes the state changes of the more sensitive parts under heat tend to be moderate, and the minor defects are not easily magnified during subsequent service.
[0020] 3. After the coupling insulating resin is coated onto the conductor surface, a continuous and relatively complete insulating coverage interface is first established. The main phase of the coating is relatively stable and is not prone to significant uneven shrinkage after cooling and shaping. Among them, after the catechol and silicon powder further enter the coating system, it does not only exist as an inorganic filler component, but also participates in the integration of the internal microstructure of the insulation layer, making the interface transition between the resin phase and the inorganic phase more balanced and the density of local areas more consistent. The coating layer formed in this way is not prone to continuous damage due to interface voids, microcracks or local unevenness during heating, stress and long-term operation. The integrity of the conductor's outer periphery barrier interface is thus easier to maintain, and it maintains a relatively stable coverage characteristic during operation. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a SEM image of the catechin-co-silicon powder prepared in Example 6 of the present invention. Detailed Implementation
[0023] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] In this application, the calcium stearate used has a purity of 98.5-99.5%, an average particle size of 2.0-2.5 μm, and a moisture content of ≤0.3 wt%; the low-density polyethylene used has a density of 0.920-0.922 g / cm³. 3 The melt flow rate is 1.4-1.8 g / 10 min (190℃, 2.16 kg); the vinyl acetate content in the ethylene-vinyl acetate copolymer used is 19-21 wt%, and the melt flow rate is 3.0-3.5 g / 10 min (190℃, 2.16 kg); the polypropylene glycol diglycidyl ether used has a number average molecular weight of 380-420, an epoxy equivalent of 190-220 g / eq, and a viscosity of 120-160 mPa·s at 25℃; the silica used is amorphous nano silica with a purity ≥99.5%, an average particle size of 30-35 nm, and a specific surface area of 180-220 m². 2 / g.
[0025] Example 1
[0026] This embodiment provides a method for preparing a coupling insulating resin, including the following steps:
[0027] Step 1: Preparation of dual-active polyolefin masterbatch
[0028] Weigh out 360.0g of low-density polyethylene and 140.0g of ethylene-vinyl acetate copolymer and add them to a mixer to mix evenly. Then add 20.0mL of vinyltrimethoxysilane, 8.0g of maleic anhydride and 2.0g of dicumyl peroxide evenly and add them to a twin-screw extruder. Control the temperature of each temperature zone at 145℃ and the screw speed at 160r / min. Extrude for 4min. After vacuum degassing, the extrudate is discharged from the machine, cooled, stretched, and pelletized. It is then placed in a drying oven at 50℃ and dried for 2h to obtain a dual-active polyolefin masterbatch with a particle size of 3.0mm.
[0029] The reaction principle for preparing dual-active polyolefin masterbatch is as follows:
[0030] Dicumyl peroxide decomposes upon heating at extrusion temperature to generate free radicals. These free radicals abstract hydrogen atoms from the molecular chains of low-density polyethylene and ethylene-vinyl acetate copolymer to form polyolefin macromolecular free radicals. Vinyltrimethoxysilane and maleic anhydride are grafted onto the polyolefin molecular chains under the initiation of free radicals, thereby introducing alkoxysilane and anhydride structures into the polyolefin backbone to obtain a dual-active polyolefin masterbatch.
[0031] Step 2: Preparation of flexible boron ester base material
[0032] Weigh 260.0 mL of polypropylene glycol diglycidyl ether and add it to the reaction vessel. Stir and heat to 58°C. Add 65.0 g of 3-amino-1,2-propanediol and keep warm and stir for 2.5 h. Then heat to 85°C and add 45.0 g of 1,4-phenylenediboric acid in batches. Keep warm and stir for 1.5 h. After the reaction is complete, cool down to 55°C and discharge the material. Place the discharged material in a vacuum drying oven at 60°C and dry for 4 h to obtain flexible boron ester base material.
[0033] The reaction principle for preparing flexible boron ester base materials is as follows:
[0034] The epoxy group in the polypropylene glycol diglycidyl ether molecule undergoes a ring-opening addition reaction with the amino group in the 3-amino-1,2-propanediol molecule to form an organic segment containing hydroxyl and amino groups; subsequently, the borate group in 1,4-phenylenediboronic acid undergoes condensation with the vicinal diol structure in the system to form a borate ester structural unit, thereby obtaining a flexible reactive base material containing ether bonds, hydroxyl groups, amino groups and borate ester structures.
[0035] Step 3: Preparation of coupling insulating resin
[0036] Weigh 450.0g of dual-active polyolefin masterbatch and add it to a mixer for 2 minutes of melting and mixing. Then add 20.0g of flexible borosilicate base material and mix at 150℃ and 50r / min for 4 minutes. After mixing, discharge the material, press it into sheets, cool it, crush it and granulate it to obtain coupling insulating resin with a particle size of 3.0mm.
[0037] The reaction principle for preparing coupling insulating resin is as follows:
[0038] The dual-active polyolefin masterbatch is melted under intensive mixing conditions to form a continuous organic phase. The flexible borate ester base material is dispersed into the polyolefin system under heat and shear, so that the resulting resin system simultaneously contains polyolefin segments, alkoxysilane grafted structures, acid anhydride grafted structures and borate ester dynamic covalent structural units, thus obtaining a coupled insulating resin.
[0039] The mechanism of action of coupling insulating resin in the insulating layer is as follows:
[0040] The coupling insulating resin obtained by this process constitutes the main resin phase of the final insulating layer. Its structure is derived from the composite configuration of continuous polyolefin segments, alkoxysilane grafted structures, acid anhydride grafted structures, and dynamic covalent structural units of borate esters. Based on this structural feature, it not only plays a role in the forming, coating, and continuous phase support of the insulating layer in the system, but also provides a relatively rich basis for interfacial interactions between the resin and inorganic components. This makes it easier for the insulating layer to form a uniform and stable covering structure. With the synergistic existence of the above-mentioned multiple structural units, the stress transmission, interfacial transition, and local deformation regulation within the coating layer become more coordinated, thereby reducing the tendency for phase boundary separation, uneven local shrinkage, and the formation of microscopic weak areas. As reflected in the final product, the insulating layer is more likely to maintain structural continuity and interfacial stability under heat, stress, and long-term operation conditions, and exhibits a more balanced tendency to maintain mechanical properties, performance retention after thermal aging, and insulation barrier state.
[0041] Example 2
[0042] This embodiment provides a method for preparing a coupling insulating resin, including the following steps:
[0043] Step 1: Preparation of dual-active polyolefin masterbatch
[0044] Weigh out 400.0g of low-density polyethylene and 160.0g of ethylene-vinyl acetate copolymer and add them to a mixer to mix evenly. Then add 25.0mL of vinyltrimethoxysilane, 11.0g of maleic anhydride and 3.0g of dicumyl peroxide evenly and add them to a twin-screw extruder. Control the temperature of each zone at 180℃ and the screw speed at 200r / min. Extrude for 8min. After vacuum degassing, the extrudate is discharged from the machine, cooled, stretched, and pelletized. It is then placed in a drying oven at 60℃ and dried for 4h to obtain a dual-active polyolefin masterbatch with a particle size of 4.0mm.
[0045] Step 2: Preparation of flexible boron ester base material
[0046] Weigh 320.0 mL of polypropylene glycol diglycidyl ether and add it to the reaction vessel. Stir and heat to 65°C. Add 82.0 g of 3-amino-1,2-propanediol and keep warm and stir for 3.5 h. Then heat to 92°C and add 60.0 g of 1,4-phenylenediboric acid in batches. Keep warm and stir for 2.5 h. After the reaction is completed, cool down to 65°C and discharge the material. Place the discharged material in a vacuum drying oven at 70°C and dry for 8 h to obtain flexible boron ester base material.
[0047] Step 3: Preparation of coupling insulating resin
[0048] Weigh out 550.0g of dual-active polyolefin masterbatch and add it to a mixer to melt and mix for 3 minutes. Then add 30.0g of flexible borosilicate base material and mix at 160℃ and 70r / min for 7 minutes. After mixing, discharge the material, press it into sheets, cool it, crush it and granulate it to obtain coupling insulating resin with a particle size of 4.0mm.
[0049] Example 3
[0050] This embodiment provides a method for preparing a coupling insulating resin, including the following steps:
[0051] Step 1: Preparation of dual-active polyolefin masterbatch
[0052] Weigh out 380.0g of low-density polyethylene and 150.0g of ethylene-vinyl acetate copolymer and add them to a mixer to mix evenly. Then add 22.5mL of vinyltrimethoxysilane, 9.5g of maleic anhydride and 2.5g of dicumyl peroxide evenly and add them to a twin-screw extruder. Control the temperature of each temperature zone at 163℃ and the screw speed at 180r / min. Extrude for 6min. After vacuum degassing, the extrudate is discharged from the machine, cooled, stretched, and pelletized. It is then placed in a drying oven at 55℃ for 3h to obtain a dual-active polyolefin masterbatch with a particle size of 3.5mm.
[0053] Step 2: Preparation of flexible boron ester base material
[0054] Weigh 290.0 mL of polypropylene glycol diglycidyl ether and add it to the reaction vessel. Stir and heat to 62°C. Add 73.5 g of 3-amino-1,2-propanediol and keep warm and stir for 3.0 h. Then heat to 89°C and add 52.5 g of 1,4-phenylenediboric acid in batches. Keep warm and stir for 2.0 h. After the reaction is completed, cool down to 60°C and discharge the material. Place the discharge material in a vacuum drying oven at 65°C and dry for 6 h to obtain flexible boron ester base material.
[0055] Step 3: Preparation of coupling insulating resin
[0056] Weigh out 500.0g of dual-active polyolefin masterbatch and add it to a mixer for 3 minutes of melting and mixing. Then add 25.0g of flexible borosilicate base material and mix at 155℃ and 60r / min for 6 minutes. After mixing, discharge the material, press it into sheets, cool it, crush it and granulate it to obtain coupling insulating resin with a particle size of 3.5mm.
[0057] Example 4
[0058] This embodiment provides a method for preparing a 1kV overhead insulated conductor that is resistant to tensile stress and aging, including the following steps:
[0059] Step 1: Preparation of catechol-co-silica powder
[0060] Weigh out 800.0 mL of deionized water and 10.0 g of tris(hydroxymethyl)aminomethane and add them to the reaction vessel. Stir, then adjust the pH to 8.4 with 10 wt% hydrochloric acid aqueous solution, add 250.0 mL of anhydrous ethanol, stir evenly, add 50.0 g of silica for dispersion, and then add 15.0 g of dopamine hydrochloride. Keep warm and stir at 28℃ for 4 h. After the reaction is completed, filter and collect the filter cake. Wash the filter cake once with anhydrous ethanol and once with deionized water, then place it in a vacuum drying oven at 45℃ for 10 h, pulverize it and pass it through a 200 mesh sieve to obtain catechol synergistic silica powder.
[0061] The reaction principle for preparing catechin-co-silicon powder is as follows:
[0062] Tris(hydroxymethyl)aminomethane maintains the reaction system under weakly alkaline conditions, under which dopamine hydrochloride undergoes oxidative self-polymerization to generate dopamine oxidative polymerization products. The silanol groups on the surface of nano-silica facilitate the adsorption and deposition of the above oxidative polymerization products on the particle surface, thereby forming an organic coating layer containing catechol structure on the surface of nano-silica, and obtaining catechol synergistic silica powder.
[0063] The mechanism of action of catechins and silicon powder in the insulating layer is as follows:
[0064] The catechin-coated silica powder obtained by this process is a functional inorganic co-component in the final insulating layer. Its structure originates from the organic coating layer containing catechins formed on the surface of silica particles. This distinguishes it from ordinary silica powder, which exists only as an inert filler dispersed in the resin system. In the system, this component retains the role of inorganic particles in local densification and structural support of the insulating layer. On the other hand, it enhances the interfacial affinity and transition coordination between itself and the main resin phase by relying on the surface organic layer. This makes it easier for it to be uniformly embedded in the continuous phase composed of the coupled insulating resin. As reflected in the final product, the filler dispersion state, interfacial connection degree and local tissue uniformity inside the insulating layer are more likely to remain stable. The tendency to form weak areas caused by interfacial voids, phase boundary discontinuities or local defects is relatively reduced. As a result, the insulating layer is more likely to maintain structural continuity, interfacial stability and coordinated insulation barrier state under heat, stress and long-term operation conditions.
[0065] Step 2: Prepare 1kV overhead insulated conductors
[0066] Weigh out the following by weight: 100 parts of the coupling insulating resin prepared in Example 1, 1.0 part of catechol synergistic silica powder, 0.21 parts of antioxidant 1010, 0.21 parts of antioxidant 168, 0.12 parts of calcium stearate, and 0.08 parts of dibutyltin dilaurate. Add these to a mixer and stir until homogeneous. Then add the mixture to an extruder, controlling the temperature of each zone at 130°C and the screw speed at 140 r / min. Melt extrude and coat the material with a cross-sectional area of 50 mm². 2An insulation layer with a thickness of 1.5 mm is formed on the surface of the conductor layer, and after natural cooling, a 1kV overhead insulated conductor is obtained.
[0067] The reaction principle for preparing 1kV overhead insulated conductors is as follows:
[0068] Coupling insulating resin, catechin synergistic silica powder, antioxidant 1010, antioxidant 168 and calcium stearate form a homogeneous melt system under heating and shearing action, which is then continuously extruded through an extruder die and coated onto the conductor surface; the coating layer changes from a molten state to a solid state during the cooling process, thereby forming an insulating layer on the outer periphery of the conductor, resulting in a 1kV overhead insulated conductor.
[0069] Example 5
[0070] This embodiment provides a method for preparing a 1kV overhead insulated conductor that is resistant to tensile stress and aging, including the following steps:
[0071] Step 1: Preparation of catechol-co-silica powder
[0072] Weigh 1000.0 mL of deionized water and 14.0 g of tris(hydroxymethyl)aminomethane and add them to the reaction vessel and stir. Then, adjust the pH to 8.6 with 10 wt% hydrochloric acid aqueous solution, add 350.0 mL of anhydrous ethanol, stir evenly, add 70.0 g of silica for dispersion, and then add 21.0 g of dopamine hydrochloride. Keep the mixture at 35 ℃ and stir for 8 h. After the reaction is completed, filter and collect the filter cake. Wash the filter cake twice with anhydrous ethanol and deionized water, and then dry it in a vacuum drying oven at 55 ℃ for 14 h. Pulverize it through a 200 mesh sieve to obtain catechol synergistic silica powder.
[0073] Step 2: Prepare 1kV overhead insulated conductors
[0074] Weigh out the following by weight: 100 parts of the coupling insulating resin prepared in Example 2, 2.0 parts of catechol synergistic silica powder, 0.32 parts of antioxidant 1010, 0.32 parts of antioxidant 168, 0.15 parts of calcium stearate, and 0.10 parts of dibutyltin dilaurate. Add these to a mixer and stir until homogeneous. Then add the mixture to an extruder, controlling the temperature of each zone at 160°C and the screw speed at 180 r / min. Melt extrude and coat the material with a cross-sectional area of 60 mm². 2 An insulation layer with a thickness of 1.5 mm is formed on the surface of the conductor layer, and after natural cooling, a 1kV overhead insulated conductor is obtained.
[0075] Example 6
[0076] This embodiment provides a method for preparing a 1kV overhead insulated conductor that is resistant to tensile stress and aging, including the following steps:
[0077] Step 1: Preparation of catechol-co-silica powder
[0078] Weigh out 900.0 mL of deionized water and 12.0 g of tris(hydroxymethyl)aminomethane and add them to the reaction vessel. Stir, then adjust the pH to 8.5 with 10 wt% hydrochloric acid aqueous solution, add 300.0 mL of anhydrous ethanol, stir evenly, add 60.0 g of silica for dispersion, then add 18.0 g of dopamine hydrochloride, keep warm at 32℃ and stir for 6 h. After the reaction is completed, filter and collect the filter cake. Wash the filter cake twice with anhydrous ethanol and deionized water, then place it in a vacuum drying oven at 50℃ for 12 h, pulverize and pass through a 200 mesh sieve to obtain catechol synergistic silica powder.
[0079] Step 2: Prepare 1kV overhead insulated conductors
[0080] Weigh out the following by weight: 100 parts of the coupling insulating resin prepared in Example 3, 1.5 parts of catechol synergistic silica powder, 0.27 parts of antioxidant 1010, 0.27 parts of antioxidant 168, 0.14 parts of calcium stearate, and 0.09 parts of dibutyltin dilaurate. Add these to a mixer and stir until homogeneous. Then add the mixture to an extruder, controlling the temperature of each zone at 145°C and the screw speed at 160 r / min. Melt extrude and coat the material with a cross-sectional area of 55 mm². 2 An insulation layer with a thickness of 1.5 mm is formed on the surface of the conductor layer, and after natural cooling, a 1kV overhead insulated conductor is obtained.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 6 is that maleic anhydride was omitted when preparing the dual-active polyolefin masterbatch in step one.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 6 is that the addition of flexible borosilicate base material is omitted when preparing the coupling insulating resin in step three.
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 6 is that the addition of dopamine hydrochloride was omitted when preparing catechol-co-silicon powder in step one.
[0087] Performance testing:
[0088] Except for the insulation resistance test, which directly used the 1kV overhead insulated conductors prepared in Examples 4-6 and Comparative Examples 1-3, all other tests were conducted by directly peeling off the insulation layer of the 1kV overhead insulated conductors prepared in Examples 4-6 and Comparative Examples 1-3, without secondary hot pressing. All samples were placed at 23±2℃ and 50±5% relative humidity for 24 hours before testing. For mechanical properties and aging resistance tests, 5 parallel samples were taken for each group, and for insulation resistance tests, 3 parallel samples were taken for each group. The test results were taken as the arithmetic mean.
[0089] Tensile strength was determined in accordance with GB / T 2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables - Part 11: General Test Methods - Thickness and Dimensional Measurements - Mechanical Properties Tests". The test results are expressed as tensile strength, with units of MPa.
[0090] The specific test methods and parameters are as follows: The insulation layer is peeled off along the conductor axis, and dumbbell-shaped specimens are prepared according to the corresponding standard method; the test is carried out using an electronic universal testing machine, and the tensile speed is fixed at 250 mm / min; each specimen is tested once, and the maximum tensile stress before fracture is recorded as the test result of the specimen; 5 parallel specimens are taken from each group, and the arithmetic mean is taken as the final result.
[0091] The elongation at break was determined in accordance with GB / T 2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 11: General Test Methods - Thickness and Dimensional Measurement - Mechanical Properties Test". The test results are expressed as elongation at break, in percentage (%).
[0092] The specific test methods and parameters are as follows: the sample preparation method, conditioning conditions, clamping method and tensile speed are consistent with those of the tensile strength test; the sample is stretched until it breaks, the elongation at break is recorded and the elongation at break is calculated according to the standard method; 5 parallel samples are taken from each group and the arithmetic mean is taken as the final result.
[0093] The tensile strength retention rate after heat aging was determined according to GB / T 2951.12-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 12: General Test Methods - Heat Aging Test Method". The tensile strength before and after aging was measured according to GB / T2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 11: General Test Methods - Thickness and Dimensional Measurements - Mechanical Properties Test". The test results are expressed as the tensile strength retention rate after heat aging, in % (%).
[0094] The specific test methods and parameters are as follows: The samples before and after aging were made from the same part of the insulation layer of the same batch of wires; the samples were placed in a natural ventilation air oven and aged at 100±2℃ for 240h; after aging, the samples were taken out and placed at 23±2℃ for 16h; then the tensile strength after aging was determined according to the method of tensile strength test, and the tensile strength retention rate after thermal aging was calculated as "tensile strength after aging / tensile strength before aging × 100%"; 5 parallel samples were taken from each group, and the arithmetic mean was taken as the final result.
[0095] The retention rate of elongation at break after thermal aging was determined according to GB / T 2951.12-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 12: General Test Methods - Thermal Aging Test Method". The elongation at break before and after aging was measured according to GB / T2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Fibers - Part 11: General Test Methods - Thickness and Dimensional Measurements - Mechanical Properties Test". The test results are expressed as the retention rate of elongation at break after thermal aging, in % (%).
[0096] The specific test methods and parameters are as follows: the heat aging conditions, recovery conditions and sample sampling locations are consistent with the tensile strength retention rate after heat aging; after aging recovery, the elongation at break after aging is determined according to the method of the elongation at break, and the elongation at break after heat aging is calculated as "elongation at break after aging / elongation at break before aging × 100%"; 5 parallel samples are taken for each group, and the arithmetic mean is taken as the final result.
[0097] The insulation resistance at 20℃ was determined in accordance with GB / T 3048.5-2007 "Test Methods for Electrical Properties of Wires and Cables - Part 5: Insulation Resistance Test", and the test conditions were unified in conjunction with GB / T 3048.1-2007 "Test Methods for Electrical Properties of Wires and Cables - Part 1: General Rules". The test results are expressed as insulation resistance at 20℃, and the unit is MΩ·km.
[0098] The specific test methods and parameters are as follows: Three sections of finished conductor samples were cut from each group, each section being 10.0m in length; 0.5m of insulation layer was removed from both ends to expose the conductor; the samples were placed at 20±1℃ until temperature equilibrium was reached before testing, without temperature conversion; the external electrode was formed by uniformly and tightly wrapping aluminum foil strips on the surface of the insulation layer, with the effective covering length of the aluminum foil strips fixed at 8.0m, and 1.0m of uncovered lead-out sections were retained at both ends of the sample; during testing, a 500V DC voltage was applied between the conductor and the external electrode, and a stable value was read after 1 minute of energization, and converted into insulation resistance per unit length according to the standard method, which was taken as the insulation resistance result of the sample at 20℃; the arithmetic mean of the three parallel samples in each group was taken as the final result, and the specific data are shown in Table 1.
[0099] Table 1 - Performance Test Data for Each Sample
[0100] Tensile strength / MPa 14.1 14.3 14.4 12.9 13.3 13.5 Elongation at break / % 24.1 24.2 24.4 20.8 19.3 22.0 Tensile strength retention rate after heat aging / % 85.4 85.7 85.9 79.2 77.6 81.0 Elongation at break retention rate after heat aging / % 79.8 80.1 80.3 72.4 69.1 74.6 Insulation resistance at 20℃ / MΩ·km 1870 1876 1879 1685 1732 1710
[0101] Data Analysis:
[0102] Comparative analysis of the data in Table 1 reveals that the 1kV overhead insulated conductor prepared by this invention exhibits a tensile strength of 14.4 MPa, an elongation at break of 24.4%, and a tensile strength retention rate of 85.9% after heat aging, while maintaining an elongation at break of 80.3% after heat aging. Furthermore, the conductor's insulation resistance at 20℃ is 1879 MΩ·km. All these data are superior to the comparative example, indicating that:
[0103] In Comparative Example 1, since the original multiple active structures in the resin matrix were not fully established, although the subsequently formed insulating layer could still maintain the basic coating morphology, the connection relationship between different components tended to be simple, and the interface region was difficult to maintain a relatively stable bonding state. As a result, the continuity of stress transmission inside the coating layer was weakened, and stress retention and preferential growth of weak parts were more likely to occur after local stress. Under the combined action of heat and force, it further evolved into structural relaxation and interface instability, thereby weakening the overall coordination of composite performance.
[0104] In Comparative Example 2, since the main system did not form the necessary coupling structure, although the material still has continuous covering characteristics after forming, it lacks the coordination relationship between support and adaptability. As a result, under continuous heating and repeated stress conditions, local deformation is difficult to disperse to the surrounding area in time, and it is not easy for the local area and the overall structure to maintain synchronous response. The state changes that could have been buffered are more likely to occur in a concentrated manner, and further cause microstructure differentiation, resulting in a decrease in the stability of the sample's overall performance.
[0105] In Comparative Example 3, since an effective synergistic transition layer was not formed on the surface of the inorganic component, although it still participated in the construction of the insulation layer after entering the resin system, the degree of interfacial integration with the main phase was insufficient, making it difficult to establish a stable and continuous microscopic connection relationship. As a result, the filler dispersion state, local density and interfacial transition consistency all decreased. Fine voids and discontinuous parts at the phase boundary were more likely to remain inside the insulation layer, and these were gradually amplified into structural weak links during subsequent thermal effects, mechanical disturbances and long-term operation, thus leading to an overall decline in composite performance.
[0106] Ultimately, it is shown that the changes in sample performance do not correspond to a linear response to the addition or subtraction of a single component. Rather, they reflect the difference in the completeness of the action chain among the main resin construction, flexible coupling formation, and interface synergistic integration in the insulation layer system. When any link fails to be established in the intended manner, the structural continuity, phase transition balance, and state synergy during operation of the material will all be affected. Consequently, local micro-defects are more likely to accumulate and externalize into overall performance fluctuations under thermal effects, mechanical disturbances, and long-term service conditions. It can be seen that the material configuration method corresponding to this scheme is not a simple parallel superposition of the functions of each component, but a systematic structure that gradually forms mutual constraints and mutual support during the preparation process. Its comprehensive performance is more due to the tendency of the structure to maintain stability under actual operating conditions.
[0107] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A 1kV overhead insulated conductor with tensile strength and aging resistance, characterized in that, It includes a conductor layer and an insulating layer, wherein the conductor layer is made of aluminum and has a cross-sectional area of 50-60 mm². 2 The insulating layer is obtained by melting and extruding insulating material onto the surface of the conductor layer, and its thickness is 1.4-1.5 mm. The insulating layer material comprises the following raw materials in parts by weight: 100 parts coupling insulating resin, 1-2 parts catechol synergistic silica powder, 0.21-0.32 parts antioxidant 1010, 0.21-0.32 parts antioxidant 168, and 0.12-0.15 parts calcium stearate, wherein the coupling insulating resin is a polyolefin-based resin containing a silane grafted structure, an anhydride grafted structure, and a borate ester dynamic coupling structure; and the catechol synergistic silica powder is a silica synergistic base material with a catechol functional layer on its surface. The preparation method of the coupling insulating resin is as follows: add the dual-active polyolefin masterbatch to the internal mixer and melt mix for 2-3 minutes, then add the flexible borosilicate base material, and mix at 150-160℃ and 50-70r / min for 4-7 minutes, and then perform post-treatment to obtain the coupling insulating resin. The ratio of the amount of the dual-active polyolefin masterbatch to the flexible borosilicate base material is 450-550g:20-30g. The preparation method of the flexible boron ester base material is as follows: polypropylene glycol diglycidyl ether is added to a reaction vessel and stirred. After heating to 58-65℃, 3-amino-1,2-propanediol is added and stirred for 2.5-3.5h. Then, the temperature is raised to 85-92℃ and 1,4-phenylenediboric acid is added in batches and stirred for 1.5-2.5h. The flexible boron ester base material is obtained after post-treatment. The method for preparing the catechin-synergistic silica powder is as follows: deionized water and tris(hydroxymethyl)aminomethane are added to a reaction vessel and stirred. Then, the pH is adjusted to 8.4-8.6 using 10wt% hydrochloric acid aqueous solution, and anhydrous ethanol is added. After stirring evenly, silica is added for dispersion, and then dopamine hydrochloride is added. The mixture is kept at 28-35℃ and stirred for 4-8 hours. The catechin-synergistic silica powder is obtained after post-treatment.
2. The 1kV overhead insulated conductor with tensile strength and aging resistance according to claim 1, characterized in that, The method for preparing the insulating layer is as follows: the insulating layer material is added to a mixer and stirred until uniform. Then the mixture is added to an extruder, and the temperature of each temperature zone is controlled at 130-160℃, the screw speed is 140-180r / min, and the mixture is melt-extruded and coated onto the surface of the conductor layer to form an insulating layer.
3. A 1kV overhead insulated conductor with tensile strength and aging resistance according to claim 1, characterized in that, The preparation method of the dual-active polyolefin masterbatch is as follows: low-density polyethylene and ethylene-vinyl acetate copolymer are added to a mixer and mixed evenly. Then, vinyltrimethoxysilane, maleic anhydride and dicumyl peroxide are mixed evenly and added to a twin-screw extruder. The temperature of each temperature zone is controlled at 145-180℃, the screw speed is 160-200 r / min, and the extrusion time is 4-8 min. The dual-active polyolefin masterbatch is obtained after post-treatment.
4. A 1kV overhead insulated conductor with tensile strength and aging resistance according to claim 3, characterized in that, The ratio of the low-density polyethylene, ethylene-vinyl acetate copolymer, vinyltrimethoxysilane, maleic anhydride and dicumyl peroxide is 360-400g:140-160g:20-25mL:8-11g:2-3g.
5. A 1kV overhead insulated conductor with tensile strength and aging resistance according to claim 1, characterized in that, The ratio of polypropylene glycol diglycidyl ether, 3-amino-1,2-propanediol and 1,4-phenylenediboronic acid is 260-320 mL: 65-82 g: 45-60 g.
6. A 1kV overhead insulated conductor with tensile strength and aging resistance according to claim 1, characterized in that, The ratio of deionized water, tris(hydroxymethyl)aminomethane, anhydrous ethanol, silica and dopamine hydrochloride is 800-1000mL:10-14g:250-350mL:50-70g:15-21g.
Citation Information
Patent Citations
Anti-aging tensile overhead insulated wire and preparation method thereof
CN118620320A
High-barrier tear-resistant PE-based packaging material and preparation method thereof
CN121203329A